THE INFLUENCE OF SOCIAL MEDIA MARKETING, DESTINATION IMAGE ON VISITING DECISIONS WITH VISITING INTEREST AS AN INTERVENING VARIABLE - Kavatina Munamahsa Islami; Rini Anggriani; Lady Faerrosa (Fakultas Ekonomi dan Bisnis Universitas Mataram, 2023)
The advancement of the internet has an impact on the increase in social media users and this is in line with the development of tourism, triggering the emergence of Instagram accounts with the theme of tourist destinations which can indirectly create an image of the destination it posts, resulting in the emergence of someone's interest in visiting. So that it triggers the decision to visit tourists. This study aims to determine the effect of social media marketing and destination image on visiting decisions with visiting interest as an intervening variable for tourists in the Mandalika Special Economic Zone (SEZ). This type of research uses descriptive quantitative with a causal approach. The sample size was 135 respondents. Data analysis tools using AMOS 24.0. The results found that social media marketing affects visiting interest. Destination image affects the interest in visiting. Social media marketing has no effect on visiting decisions. Destination image has no effect on visiting decisions. Social media marketing has a positive and insignificant effect on visiting decisions through visiting interest. Destination image has a positive and insignificant effect on visiting decisions through visiting interest. From the results of the study, it can be concluded that visiting interest will increase if social media marketing is utilized properly and improves destination image, so that it can trigger the formation of visiting decisions. Suggestions for the government and business actors are to continue to develop tourist attractions in SEZ Mandalika by adding facilities and protecting the environment